2004
DOI: 10.1096/fj.04-2695fje
|View full text |Cite
|
Sign up to set email alerts
|

Turning on stem cell cardiogenesis with extremely low frequency magnetic fields

Abstract: Modulation of stem cell differentiation is an important assignment for cellular engineering. Embryonic stem (ES) cells can differentiate into cardiomyocytes, but the efficiency is typically low. Here, we show that exposure of mouse ES cells to extremely low frequency magnetic fields triggered the expression of GATA-4 and Nkx-2.5, acting as cardiac lineage-promoting genes in different animal species, including humans. Magnetic fields also enhanced prodynorphin gene expression, and the synthesis and secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 16 publications
0
67
0
5
Order By: Relevance
“…However, current methods are experiencing poor yields in terms of cells that migrate to damaged areas and then differentiate into a desired cell type. A new study by Ventura et al [2005] has demonstrated the ability of 0.8 mT (rms) 50 Hz magnetic fields to influence stem cell differentiation, increasing the number of cells that become myocardial cells. Using electric field stimulation Sauer et al [1999] increased stem cell differentiation into cardiomyocytes via a reactive oxygen species mechanism.…”
Section: Repairing the Damagementioning
confidence: 99%
“…However, current methods are experiencing poor yields in terms of cells that migrate to damaged areas and then differentiate into a desired cell type. A new study by Ventura et al [2005] has demonstrated the ability of 0.8 mT (rms) 50 Hz magnetic fields to influence stem cell differentiation, increasing the number of cells that become myocardial cells. Using electric field stimulation Sauer et al [1999] increased stem cell differentiation into cardiomyocytes via a reactive oxygen species mechanism.…”
Section: Repairing the Damagementioning
confidence: 99%
“…Real-time quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) analysis revealed a remarkably increased of GATA-4 and Nkx-2.5 mRNA expression for both embryoid bodies (EBs) and puromycinselected cardiomyocytes [25]. Hence, the result of exposing GTR1 embryonic stem cells with this MF was the differentiation into cardiac specific cells, and this experiment was done without an aid of gene transfer technology [25].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) analysis revealed a remarkably increased of GATA-4 and Nkx-2.5 mRNA expression for both embryoid bodies (EBs) and puromycinselected cardiomyocytes [25]. Hence, the result of exposing GTR1 embryonic stem cells with this MF was the differentiation into cardiac specific cells, and this experiment was done without an aid of gene transfer technology [25]. As for information, GATA-4 and Nkx-2.5 mRNA encode respectively for a zinc finger containing transcription factor and homeodomain, and both of these have been shown to be essential for cardiogenesis in different animal species [40], [41], and human [42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on extremely low frequency (ELF)-MF have showed that exposure to these fields can affect biological functions such as RNA transcription, cell viability, cell proliferation although it is unknown which molecular mechanisms are involved (Babincova et al 2000;Ventura et al 2005;Williams et al 2006;Kroupova et al 2007;Novak et al 2007;Cellini et al 2008). Still it is not still clear whether ELF-MF exposure can represent a stress factor for the cells.…”
mentioning
confidence: 99%